(untitled) - Fryer, Donald W. (New York, 1970)
Since 2000, Southeast Asia has had some of the fastest growing economies in the world. Indonesia’s economy has enjoyed 6 percent annual growth—but will its lack of infrastructure and its commodity dependence soon reveal some cracks in its economy? The remarkable growth in the Philippines will not last unless domestic investment is elevated. Thailand’s growth has stalled amid political turmoil, and it is currently in a classic credit bubble. Vietnam still generates impressive growth, but it has a banking problem, high inflation, and ubiquitous corruption. Are these four countries in danger of becoming ensnared in the classic middle-income trap (MIT)—the oft-observed slowdown in growth that occurs once developing countries reach middle-income levels? This Heritage Foundation Special Report explores these countries’ MIT risks—and explains how they can avoid, or escape, this trap.
Keywords: Southeast Asia,Đông Nam Á; Economic conditions,Điều kiện kinh tế